Internal audit and enterprise risk management in financial institutions in ghana. - Ekow Duku Colerangle (KNUST, 2024)
A thesis submitted to the department of accounting and finance, school of business, kwame nkrumah universityof science and technology in partial fulfilment of the requirements for the award of the degree of master of science in accounting and finance